Sperm Quality Affected by Naturally Occurring Chemical Elements in Bull Seminal Plasma - Filip Tirpák; Marko Halo; Marián Tomka; Tomáš Slanina; Katarína Tokárová; Martyna Błaszczyk-Altman; Lucia Dianová; Peter Ivanič; Róbert Kirchner; Agnieszka Greń; Norbert Lukáč; Peter Massányi (MDPI AG, 2022)
This study monitored the chemical and biochemical composition of bovine seminal plasma (SP). Freshly ejaculated semen (n = 20) was aliquoted into two parts. The first aliquot was immediately assessed to determine the sperm motion parameters. Another motility measurement was performed following an hour-long co-incubation of spermatozoa with SP at 6 °C. The other aliquot was processed to obtain the SP. Seminal plasma underwent the analyses of chemical composition and quantification of selected proteins, lipids and RedOx markers. Determined concentrations of observed parameters served as input data to correlation analyses where associations between micro and macro elements and RedOx markers were observed. Significant correlations of total oxidant status were found with the content of Cu and Mg. Further significant correlations of glutathione peroxidase were detected in relation to Fe and Hg. Furthermore, associations of chemical elements and RedOx markers and spermatozoa quality parameters were monitored. The most notable correlations indicate beneficial effects of seminal Fe on motility and Mg on velocity and viability of spermatozoa. On the contrary, negative correlations were registered between Zn and sperm velocity and seminal cholesterol content and motility. Our findings imply that seminal plasma has a prospective to be developed as the potential biomarker of bull reproductive health.